L’entrepreneuriat féminin au niveau de la wilaya de Tipaza Female entrepreneurship in Tipaza province - Himrane, Mohammed (Finance and Business Economies Review, 2019)
The aim of this study is to draw up an inventory of women-owned businesses in the province of Tipaza. In fact, we collected data about women entrepreneurs from various public bodies charged of management and business registration (Andi, Cnac, Angem, Ansej, Cnrc and Casnos) in Tipaza. The results show that the creation rate of womenowned businesses is very low at all public bodies. In addition, the women-owned businesses are mostly activating in the service sector and also very small.